A novel In-situ Enzymatic Cleaning Method for Reducing Membrane Fouling in Membrane Bioreactors (MBRs) - M. R. Bilad; M. Baten; A. Pollet; C. Courtin; J. Wouters; T. Verbiest; Ivo F J. Vankelecom (Universitas Pendidikan Indonesia, 2016)
A novel in-situ enzymatic cleaning method was developed for fouling control in membrane bioreactors (MBRs). It is achieved by bringing the required enzymes near the membrane surface by pulling the enzymes to a magnetic membrane (MM) surface by means of magnetic forces, exactly where the cleaning is required. To achieve this, the enzyme was coupled to a magnetic nanoparticle (MNP) and the membrane it self was loaded with MNP. The magnetic activity was turned by means of an external permanent magnet. The effectiveness of concept was tested in a submerged membrane filtration using the model enzyme-substrate of Bacillus subitilis xylanase-arabinoxylan. The MM had almost similar properties compared to the unloaded ones, except for its well distributed MNPs. The enzyme was stable during coupling conditions and the presence of coupling could be detected using a high-performance anion-exchange chromatography (HPAEC) analysis and Fourier transform infrared spectroscopy (FTIR). The system facilitated an in-situ enzymatic cleaning and could be effectively applied for control fouling in membrane bioreactors (MBRs).